Empowering Entrepreneurs: Financial Strategies for Community-based SME - Anggara, Bayu; Djamaluddin, Agus Satya (Manunggal Halim Jaya, 2024)
This study examines financial strategies for community-based Small and Medium Enterprises (SMEs) to understand how tailored interventions can address the unique challenges they face. The research aims to explore the effectiveness of microfinance, peer-to-peer (P2P) lending platforms, and capacity-building initiatives in empowering entrepreneurs and fostering SME development within local communities. Adopting a qualitative research methodology, the study employs a case study design to gather rich insights from multiple community-based SMEs across different industries and geographical locations. Data is collected through semi-structured interviews with key stakeholders and supplemented by observation techniques and documentary analysis. Thematic analysis is used to identify recurring themes, patterns, and categories, with interpretive techniques such as narrative analysis employed to elucidate underlying meanings. The findings highlight the importance of tailored financial interventions, including microfinance and P2P lending, in promoting financial inclusion and empowering entrepreneurs. Capacity-building initiatives are also shown to enhance SME resilience and competitiveness by equipping owners with essential skills and resources. However, challenges such as limited access to formal financial services, inadequate financial literacy, and regulatory constraints persist, necessitating comprehensive policy interventions and ecosystem development efforts. This study contributes to a nuanced understanding of SME financing and management dynamics, offering insights for policymakers, financial institutions, and SME owners to promote inclusive growth and sustainable development within local communities.